2014
DOI: 10.1007/s11207-014-0645-0
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Pattern of Cosmic-Ray Modulation During Solar Cycles 23 and 24

Abstract: By means of an analysis of data from eight neutron monitor (NM) stations with different geomagnetic cutoff rigidities, we found an unusual latitudinal effect observed in the cosmic-ray (CR) modulation during the last solar cycles. Since the beginning of the ground-based cosmic-ray monitoring, it is known that the solar-cycle modulation is more evident in data from high latitude than from the medium and low latitudes, showing an expected geomagnetic cutoff rigidity effect. However, a more detailed look shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
3
6
0
1
Order By: Relevance
“…The parameters to obtain these results are summarised in Table 1 and it is clear that: 1) the diffusion was required to continually increase from 2006 to 2009, with the value of κ ||,0 increasing from 16.0 in 2006 to 17.1, 17.5, and 19.4 in 2007, 2008, and 2009 respectively; 2) the spectra became progressively softer towards 2009, so that the rigidity dependence of the diffusion coefficient below ∼ 3 GeV was required to change from P 0.85 in 2006 to P 0.81 , P 0.78 , and P 0.73 2007, 2008, and 2009. These type of changes are in agreement with those found by various other authors, including Bazilevskaya et al (2012), Ndiitwani et al (2013), Potgieter et al (2014), and Pacini and Usoskin (2015). Except for providing evidence for the applicability of the SBM in particular, this qualitative correspondence in modulation results over the entire solar minimum period of 2006 to 2009 also illustrates the already well established credibility of the SDE-based model.…”
Section: The Effect On Modulationsupporting
confidence: 91%
“…The parameters to obtain these results are summarised in Table 1 and it is clear that: 1) the diffusion was required to continually increase from 2006 to 2009, with the value of κ ||,0 increasing from 16.0 in 2006 to 17.1, 17.5, and 19.4 in 2007, 2008, and 2009 respectively; 2) the spectra became progressively softer towards 2009, so that the rigidity dependence of the diffusion coefficient below ∼ 3 GeV was required to change from P 0.85 in 2006 to P 0.81 , P 0.78 , and P 0.73 2007, 2008, and 2009. These type of changes are in agreement with those found by various other authors, including Bazilevskaya et al (2012), Ndiitwani et al (2013), Potgieter et al (2014), and Pacini and Usoskin (2015). Except for providing evidence for the applicability of the SBM in particular, this qualitative correspondence in modulation results over the entire solar minimum period of 2006 to 2009 also illustrates the already well established credibility of the SDE-based model.…”
Section: The Effect On Modulationsupporting
confidence: 91%
“…Solomon et al (2011) attribute the Earth's lower thermospheric density during the 2008 minimum, as evidenced by drag measurements of Earth-orbiting spacecraft, to be due to lower levels of extreme-ultraviolet solar-irradiance. Similarly, Pacini and Usoskin (2015) use neutron-monitor records from eight Earth-based stations to show an increase in polar cosmic-ray intensities during the 2008 solar minimum from the prior three, which they attribute to changes in the solar wind. While such independent observations are indicative of lower solar activity during this recent solar minimum and may be corroborative of possibly-similar secular trends in TSI-variations during the 2008 solar minimum.…”
Section: Secular Variability Over the Space-borne Measurement Eramentioning
confidence: 99%
“…It is, e.g., suggested that during periods of very weak solar activity (like the Maunder Minimum), the relation between solar activity and cosmic rays may be inverted [16]. The new features found at the heliospheric modulation of GCR measured by ground-based detectors are discussed in [17] and references therein.…”
Section: In the Heliospherementioning
confidence: 95%